Pemberdayaan Perempuan Melalui Pelatihan Tata Kecantikan Rambut di Sanggar Kegiatan Belajar (SKB) Kabupaten Banjarnegara - Febrina Rachma Fatana; Sungkowo Edy Mulyono (Journal on Education, 2023)
The problem in this research is poverty which continues to increase due to the low quality of human resources especially women. The purpose of this research was to describe the process of empowering women through training in hairstyling at SKB Banjarnegara. This research is a descriptive study using a qualitative approach. There were six research subjects, namely the head of the SKB, program coordinator, training instructor and three trainees. Data collection techniques using observation techniques, interviews and documentation. The validity of the data using source triangulation and technique triangulation. Data analysis techniques include data collection, reduction, data display, conclusions. The results of the study explain that the training process is divided into three stages, planning, implementation, and evaluation. Planning is determined by setting training objectives. Infrastructure facilities are adjusted to the regional budget 2 of Banjarnegara. Recruitment of competent training instructors and recruitment of 10 trainees. Implementation of training for 60 hours as many as 20 meetings. The basic training material is adjusted to the conditions of the participants. Communication occurs in two directions well but it needs to improve a conducive learning atmoshphere. The training media is in the form of modules and salon equipment. The training method is in the form of lectures, practice, questions and answer and discussion. Constructive motivation is carried out by the instructor to the participants. The evaluation stage through pre test and post test was carried out before and after the written training. Process evaluation is carried out during the training activities. Program evaluation is carried out at the end of the activity to improve the implementation of the training in the following year. Follow up by channeling participants who are interested in apprenticing at the training instructor’s salon.